WHAT HAPPENS TO ACCOUNTING MAJORS? - Yankee, Glen G.; Dilley, Merrill B. (The Accounting Review, 1961)
This article summarizes the information provided by 95% of the living accounting graduates of Drake University, Des Moines, Iowa who responded to a written questionnaire during the winter of 1959-60. This survey resulted in considerable data on occupation by function, job titles, geographical location, and income of accounting graduates. Approximately sixty-two per cent of all accounting graduates over this 38 year span are currently engaged in accounting work of some type. An additional twenty six percent are in some phase of management, including many who are doing accounting work at that level. The next largest group, totaling six per cent is engaged in sales or sales management. The remaining six per cent of the graduates are in other occupations. Income statistics were reported for over 90% of the 544 graduates covered. Although statistics were compiled for each graduating class, only the classes of 1929, 1939, 1949, and 1959 are presented here. Analysis of income data for all graduating classes would seem to indicate that accounting graduates employed in public accounting receive considerably greater income on the average both ten years and twenty years after graduation than those in other types of jobs.